Surveys of Food Deserts and Adherence to a Mediterranean Diet Among University Students. - RESTREPO YEPES, Olga Cecilia; DUQUE CHICA, Gloria Liliana; QUICENO SIERRA, Japcy Margarita; VINACCIA, Stefano; PALACIO MESA, Rubën Darío; MOLINA SALDARRIAGA, César Augusto (Nutrición Clínica y Dietética Hospitalaria, 2022)
Objective: The objective of this study was to determine and describe the presence of institutional food deserts based on access to healthy food via a level of adherence to a Mediterranean diet in higher education Metropolitan Area institutions in Valle de Aburrá, Colombia. Materials and methods: The Food Deserts Survey -EDA and the Mediterranean Diet Adherence Test -KIDMED was administered to 419 university students. Results and Discussion: Results evidenced that participants had an average adherence (58.5%) to a Mediterranean diet, indicating that university students need to improve their dietary pattern to adapt it to a Mediterranean model. Regarding the EDA, most reported that the food they consumed was nutritious (69.0%), fresh (77.3%) and healthy (61.3%). They stated they usually ate breakfast (74.7%), lunch (44.2%) and dinner (85.0%) at home during the week, and usually bought and consumed food in supermarkets and traditional stores (73.3%). Conclusion: The study concluded that regardless of gender, participants need to improve their dietary pattern to adapt it to a Mediterranean model, which could indicate a hidden presence of food deserts.